Ivabradine monotherapy in congenital junctional ectopic tachycardia - Sivalingam Devaprasath; Siddartha Buddhavarapu; Suja Mariam; Mani Ram Krishna (Wolters Kluwer Medknow Publications, 2022)
Congenital JET (junctional ectopic tachycardia) is a rare and often difficult to treat tachyarrhythmia in young infants. The addition of Ivabradine to standard Congenital JET therapy has been shown to improve arrhythmia control. However, Ivabradine has not been reported as a single drug in the control of congenital JET. We report a pre-term neonate in whom Ivabradine monotherapy was successful in treating congenital JET.